Agricultural supply chains and industry 4.0 : technological advance for sustainability /: technological advance for sustainability. (2021) - Despoudi, Stella; Spanaki, Konstantina; Rodríguez-Espíndola, Oscar; Zamani, Efpraxia D
No abstract available